Verba Bahasa Bali dalam Ranah Pertanian di Kecamatan Karangasem (Kajian Metabahasa Semantik Alami) - Ni Komang Aryani Aryani; I Kadek Widiantana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research aims to determine the natural semantic metalanguage of Balinese verbs in the agricultural domain in Karangasem District. This research is a qualitative descriptive study. The location of this research is in the village of Bugbug which is one of the villages that has a large agricultural land in Karangasem District. The informant determination technique used is purposive sampling. The data collection used is observation, interview techniques, and documentation. The stages of data analysis techniques in this study are data reduction, data presentation and concluding drawings. The results showed that there are 4 categories of Balinese verbs used in agriculture, namely; 1) verbs in the land preparation category, that is, there are 11 Balinese verbs, 2) the nursery and planting category verbs, there are 6 Balinese verbs, 3) the maintenance category verbs are 11 Balinese verbs, 4) the harvest category verbs are 9 Balinese verbs.